Upregulated claudin‐1 expression confers resistance to cell death of nasopharyngeal carcinoma cells - Lee, Jeng‐Woei; Hsiao, Wei‐Ting; Chen, Hsia‐Yun; Hsu, Lee‐Ping; Chen, Peir‐Rong; Lin, Ming‐Der; Chiu, Shu‐Jun; Shih, Wen‐Ling; Hsu, Yih‐Chih (International journal of cancer, 2010)
Accumulating evidence reveals that aberrant expression of claudins manifests in various tumors; however, their biological functions are poorly understood. Here, we report on the elevated expression of claudin‐1 in nasopharyngeal carcinoma (NPC) cell lines under serum deprivation or fluorouracil (5‐FU) treatment. Interestingly, an increase in expression of claudin‐1 considerably reduced apoptosis rather than enhancing cell proliferation. However, claudin‐1 expression and activity were unaffected by external stimuli or Akt and NF‐κB activation. Notably, predominant cytoplasmic and nuclear localization of claudin‐1 in NPC cells reflected the aforementioned feature. On the other hand, loss of epithelial morphology and E‐cadherin expression was associated with serum withdrawal in NPC cells. Interestingly, restoration of E‐cadherin inhibited the protein elevation and antiapoptotic activity of claudin‐1. In conclusion, our data demonstrate the regulation and novel biological function of claudin‐1 and indicate the important role of claudin‐1 in NPC tumorigenesis.